(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The cognitive aspect of the goal of teaching foreign languages is associated with such categories as knowledge, thinking and understanding processes involved in the process of introducing the student to a foreign language, to the culture of the people - its carrier. When determining the essence of the cognitive aspect of the goal of teaching foreign languages, it is important to proceed from the understanding that the language reflects the interaction between psychological, communicative, functional and cultural factors.